King Street, Dawson, Yukon Territory, 1899. - Hegg & Co.
Looking east. Caption on image: "Dawson, Y.T." Street scene showing ticket office for Steamboat WILLIE IRVING, Canadian Development Company offices, the Melbourne Hotel, and dental, real estate and law offices. >PH Coll 246.47 Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number